Protocol for the maximum aerobic power (MAP) evaluation test - Hutsebaut, P.; Brunet, K. (2002)
This document contains the protocol for the fitness evaluation test developed by the Canadian Cycling Association (CCA). This test was developed to estimate and describe, in the most valid manner possible: 1. the maximum aerobic power (MAP) while cycling; 2. the maximal oxygen uptake (VO2max); 3. the evolution pattern of the heart rate as power output increases; 4. the evolution pattern of blood lactate levels as power output increases; 5. the athlete`s maximum heart rate.